PHYSICAL ATTRIBUTES, ORGANIC SOIL MATERIAL AND CAPIM MARANDU PRODUCTION IN THE CROP-LIVESTOCK-FOREST INTEGRATION SYSTEM - Souza, J. F. D.; Perusso, R. L. S.; Bonini, C. S. B.; Souza, C. T.; Lupatini, G. C.; Andrighetto, C.; Mateus, G. P.; Pedro, F. G. (Revista Brasileira de Engenharia de Biossistemas, 2019)
The crop-livestock-forest integration system has the characteristic of integrating crops pastures, arboreal components and herbivorous animals in the same area. The present work had the objective of studying the physical attributes and organic matter of a dystrophic Red Latosol in a crop-livestock-forest integration system that is being conducted since 2012, as well as the production of Marandu grass. The experimental design was a randomized complete block design, with four replications and four treatments: T1 - crop - livestock integration (ILP); T2 - agrosilvipastoral system, with 1-line eucalyptus shading (ILPF 1L); T3 - agrosilvipastoril system, with shading of 3 eucalyptus lines (ILPF 3L); and T4 exclusive plantation of eucalyptus (forest). The attributes studied during the period from June 2017 to May 2018 were evaluated. Aggregate stability, soil porosity (macro and micro), soil water infiltration, mechanical penetration resistance and soil moisture were evaluated. and dry matter production of forage. The results show that there was a significant difference for macroporosity and penetration resistance. The highest forage production was observed in T1 where there was no shading effect.